Desain Pembelajaran Bilangan Berpangkat Melalui Inkuiri Terbimbing Menggunakan Google Jamboard - Tiana Virawanti; Dedi Muhtadi; Redi Hermanto (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2022)
This study aims to determine the role of the amoeba breeding context and to produce students' learning trajectories in learning rank numbers through a guided inquiry learning model using Google Jamboard. This research method uses Design Research (DR), which includes 3 stages: preliminary design), experimental design, and retrospective analysis. The research begins with a literature review and designing the HLT. The learning design was prepared based on the HLT which was then tested through 2 stages, namely the pilot experiment and teaching experiment. A retrospective analysis was performed at each stage by comparing the initial HLT with the actual learning trajectory. The data collection techniques used were observation, recording of learning activities during experimental design, giving LKPD, giving evaluation questions, and interviews. This research was conducted on students of SMP Negeri 5 Tasikmalaya class IX-B at the pilot experiment and IX-A at the teaching experiment. The results of this study indicate that the role of the Amoeba breeding context can help facilitate students to build basic concepts in finding the concept of exponent number material. In addition, a learning trajectory is produced that can help students understand the concept of rank number material, with the context of Amoeba breeding through guided inquiry using Google Jamboard.